EXCHANGE RATE DEVALUATION, ECONOMIC GROWTH AND PRICE STABILITY IN NIGERIA - BALOGUN, WAKILAT O. (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
The study explores the relationship between devaluation and growth in Nigeria using time series data from 1991 to 2023. The estimating techniques are both the Autoregressive Distributed Lag model and Granger causality test. Two models are developed for this study. The first model of ARDL explores the influence of currency devaluation on economic growth using exchange rate as the proxy for devaluation and it is one of the independent variables. Gross Domestic Product growth rate is used to represent economic growth. The second estimating technique of Granger causality tries to see whether exchange rate devaluation would lead to price instability. Results indicate no significant effect of real exchange rate on growth rate of GDP. Exchange rates Granger causes consumer price index. The study recommends that the authority should provide the enabling environment that would encourage local businesses and boost domestic production so as to ease pressure on foreign exchange.